2022
DOI: 10.1093/ejcts/ezac148
|View full text |Cite
|
Sign up to set email alerts
|

Days alive and out of hospital after enhanced recovery video-assisted thoracoscopic surgery lobectomy

Abstract: OBJECTIVES Days alive and out of hospital (DAOH) integrates overall information of hospitalization, readmissions, and mortality that have been applied as a new outcome measure. However, DAOH after video-assisted thoracoscopic surgery (VATS) in an established enhanced recovery after surgery (ERAS) programme has not been reported. METHODS Patients aged ≥18 years with non-small-cell lung cancer undergoing VATS lobectomy in an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We found that indices measuring overall variability of the heart rate (SDNN and TP) were markedly reduced after VATS lobectomy, especially in the day-and nighttime, showing only slight signs of returning towards baseline at the end of the study 9 days after surgery. This cohort seemed to be a representative sample of the patients treated at our institution, as they were similar to a previous larger cohort [14].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We found that indices measuring overall variability of the heart rate (SDNN and TP) were markedly reduced after VATS lobectomy, especially in the day-and nighttime, showing only slight signs of returning towards baseline at the end of the study 9 days after surgery. This cohort seemed to be a representative sample of the patients treated at our institution, as they were similar to a previous larger cohort [14].…”
Section: Discussionmentioning
confidence: 66%
“…While the most important reason for prolonged hospital stay after VATS is air leak, other key reasons are: pain, pneumonia, and PoAF [11,14]. Preoperative HRV has shown promise in predicting pain, pneumonia, and PoAF in preliminary studies, in other surgical settings including thoracic surgery [1,15], and has been associated with differing trajectories of molecular in ammatory responses following abdominal surgery, including higher CRP in the group of patients with lower short-term variation [19], suggesting an association between in ammation and HRV changes.…”
Section: Discussionmentioning
confidence: 99%
“…DAOH integrates overall information of hospitalisation, readmission, and mortality and as such may be important for defining future improvement strategies with the patient in focus. After implementation of ERAS median DAOH after one year postoperatively was 359 days (15).…”
Section: Discussion/perspectivesmentioning
confidence: 99%
“…Patient-centred care remains at the very heart of ERAS pathways, and patient-reported measures (such as Quality of Recovery Score-15 or WHO Disability Assessment Schedule 2.0 at 30 and 90 days after surgery) become important [21]. A recently described patient-centred outcome measurement is days alive and out of hospital within a specified time frame (30, 60, 90, 180 days or 1 year) and has recently been used to assess video-assisted thoracoscopic surgery within an ERAS programme [22].…”
Section: Healthcare Outcomes Within Enhanced Recovery After Surgerymentioning
confidence: 99%